2009
DOI: 10.1111/j.1748-5827.2009.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of small‐bore wire‐guided chest drains for management of pleural space disease

Abstract: Small-bore wire-guided chest drains are an effective alternative to larger gauge drains. Only minor complications were seen during insertion of the chest drains, and their performance was deemed satisfactory in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 17 publications
7
73
1
Order By: Relevance
“…A potential disadvantage often cited is the risk of occlusion of the narrow bore tube with thicker effusions, e.g., pyothorax; however, in a recent veterinary study this was not found to be a significant problem. 20 The small size of these drains results in a significant reduction in postoperative morbidity, particularly in cats due to their relative smaller chest size and therefore the author considers these thoracic drains to be optimal for use in the majority of feline patients.…”
Section: Closed Suction Drain Removalmentioning
confidence: 98%
“…A potential disadvantage often cited is the risk of occlusion of the narrow bore tube with thicker effusions, e.g., pyothorax; however, in a recent veterinary study this was not found to be a significant problem. 20 The small size of these drains results in a significant reduction in postoperative morbidity, particularly in cats due to their relative smaller chest size and therefore the author considers these thoracic drains to be optimal for use in the majority of feline patients.…”
Section: Closed Suction Drain Removalmentioning
confidence: 98%
“…2,16 In this technique the tube is advanced into the thorax with the use of a guidewire that has been inserted through a small needle. 2,16 In this technique the tube is advanced into the thorax with the use of a guidewire that has been inserted through a small needle.…”
Section: Active Drainage Techniquesmentioning
confidence: 99%
“…2,15 Thoracostomy tube use has been related to increased survival. 17 Lavage was performed two to six times daily and none of the tubes became occluded, suggesting that they can be successfully used and potentially reduce the morbidity associated with the large-bore tubes. 2 The use of routine lavage in feline pyothorax is controversial; however, the cats in the more recent studies underwent therapeutic lavage with isotonic saline or compound sodium lactate, with the occasional addition of an antibiotic solution.…”
Section: Chylothoraxmentioning
confidence: 99%